Town Fathers and Urban Continuity: The Roots of Community Power and Physical Form in Hamilton, Upper Canada in the 1830s - Doucet, Michael; Weaver, John (Urban History Review / Revue d'histoire urbaine, 1984)
This article is both an empirical inquiry and a theoretical declaration. It stresses, in opposition to a view of urban history that presents fairly distinct periods, that there are very important elements of continuity. Indeed, continuity may be the essence of the urban experience in Canada, especially across the nineteenth and twentieth centuries. The layout of the city, the vital promotional actions of the civic elite, a concentration of wealth, and the spatial expression of economic and social traits all have deep roots — extending to the earliest decades in the case of Hamilton, which is the site for this study.In terms of source materials, this article employs an 1839 assessment manuscript, but warns that such material can be abused or misunderstood. Indeed, it raises questions about American studies that have attempted comparisons of concentrations of property wealth over time. The article argues that a vital ingredient of wealth and power was and is the intangible factor of access to credit. That access is a feature of metropolitanism, an historiographic theme which too indicates continuity in the history of urban Canada.